The nut job 2 [videorecording (DVD)] : nutty by nature - Brunker, Cal (Universal Pictures Home Entertainment, 2017)
Surly Squirrel and the gang are back. They are once again in Oakton where the evil mayor has decided to bulldoze Liberty Park and build a dangerous amusement park in its place. Surly and his ragtag group of animal friends band together to save their home, defeat the mayor, and take back the park.